Alien shrimps in evidence: new records of the genus Athanas Leach, 1814 on the coast of So Paulo, southern Brazil (Caridea: Alpheidae) - Almeida, Alexandre O.; Simoes, Sabrina M. [UNESP]; Costa, Rogério Caetano da [UNESP]; Mantelatto, Fernando L. (Springer, 2012)
The occurrence of two alien alpheid shrimps of the genus Athanas Leach, 1814 [in Leach 1813-1814], the Indo-West Pacific A. dimorphus Ortmann, 1894 and the Eastern Atlantic A. nitescens (Leach, 1813 [in Leach 1813-1814]), on the coast of the state of So Paulo, Brazil, is reported. The presence of A. dimorphus extends the range of this species in the western Atlantic farther to the south in Brazil, whereas A. nitescens is reported for the first time in the western Atlantic, representing the second alien alpheid species on this side of the Atlantic and the twenty-first decapod crustacean introduced in Brazil. We provide morphological accounts of the material examined and illustrate the most important diagnostic characters of both species. An overview of the possible mechanisms of their introduction on the coast of So Paulo is also provided.
Keywords: Crustacea; Decapoda; Athanas; Exotic species; Western Atlantic